PEMBELAJARAN TARI MELINTING MENGGUNAKAN MODEL DISCOVERY LEARNING DI SMA NEGERI 07 BANDAR - Rien Gusmi Marisa; Hasyimkan Hasyimkan; Susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2015)
The research purpose was to discribe the process of Melinting dance learning result by using discovery learning model at SMA N 07 Bandar Lampung. This research was using descriptive qualitative research design with sources of data in study were 39 students and teacher. Data collection techniques used in this research were observation, interview, documentation, test and nontest. Discovery learning model began with 5 stage of learning, they were stimulation, problem statement, data collection, data proscessing, verification, and generalization. The result of student observation in the learning process of Melinting dance by using discovery learning model obtainedan an average value of 62 with a sufficient criterion. Practice test result was in good criteria with an average value of 79.Penelitian ini bertujuan mendeskripsikan proses dan hasil pembelajaran tari Melinting menggunakan model Discovery Learning di SMA Negeri 07 Bandar Lampung. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan sumber data guru dan siswa. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dokumentasi, tes praktik, dan nontes. Model Discovery Learning memiliki 5 tahap pembelajaran yaitu pemberian rangsangan, identifikasi masalah, pengumpulan data, pengolahan data, pembuktian, menarik kesimpulan. Hasil pengamatan aktivitas siswa dalam proses pembelajaran tari Melinting menggunakan model Discovery Learning mendapat niali 62 dengan kriteria cukup. Hasil tes praktik mendapat nilai 79 tergolong dalam kriteria baik.Kata kunci : pembelajaran, tari melinting, model discovery learning.